Hypersilyl substituent in heavier low-valent group 14 chemistry - Gour, Kritika; Bisai, Milan Kumar; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2022)
The isolation of unusual compounds with low-valent main-group elements would not have been possible without the development of a series of sterically demanding ligands with bulky substituents. While early literature recognizes the advent of the sterically demanding tris(trimethylsilyl)silyl (SiMe3)(3)Si- group, also known as hypersilyl group, to stabilize species with new coordination modes for the main group elements, it has largely been more recent studies that have utilized this group for isolating stable compounds with low-valent main-group elements. Such compounds are not only interesting from the structure-bonding point of view but showcase potential for small molecule activation under ambient conditions. This review will cover the recent developments in stabilizing unusual compounds with group 14 elements using the exceptionally strong sigma-donor properties and pronounced steric effects of the hypersilyl moiety, emphasizing their synthesis, structure, and reactivity.
Keywords: Germylenes; Hydroboration; Hypersilyl; silylenes; Stannylenes

Hypersilylsilylene-supported Ni(0) toluene and Ni(II) complexes with catalytic application - Ajithkumar, V. S.; Bisai, Milan Kumar; Ghanwat, Pratiksha B.; Raj, K. Vipin; Singh, Geetika; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2025)
The reaction of Ni(COD)2 with [PhC(NtBu)2SiSi(SiMe3)3] (1) in toluene results in the formation of an 18-electron silylene-Ni(0) toluene complex (2). The analogous reaction with 1,3-DFB instead of toluene affords the C-H activation followed by ring walking leading to the allylic cyclooctene adduct, the (eta 3-C8H13)Ni(II) complex (3). DFT calculations were carried out to elucidate the mechanism as well as to gain insight into why 1,3-DFB undergoes C-H bond activation instead of C-F bond activation. The use of NiCl2DME permits access to 16-electron (tetrylene)2NiCl2 (Si(4) and Ge(5)) species, and 4 was later used as a catalyst for the C-N coupling reaction.